Foreign object damage simulation of aero-engine blade. (November 2020) - Xie, Zhenbo; Ma, Zhongyuan; Chen, Qinggui; Li, Bianjiang; Zhao, Zhenhua
Abstract: To study the anti-foreign object damage (FOD) ability of aero-engine compressor blades, finite element model of compressor blades was established. Blades damage was evaluated with different steel ball diameters and shock angles. Results show that the damage width and depth becomes bigger with the steel ball's diameter increases. The damage width doesn't change apparently with the shock angles, and the damage width nearly equals to the steel ball diameter. The damage depth mostly becomes smaller with the increase of shock angle.